1994
DOI: 10.1126/science.8171324
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Granulocyte-Macrophage Colony-Stimulating Factor in Pulmonary Homeostasis

Abstract: The in vivo function of murine granulocyte-macrophage colony-stimulating factor (GM-CSF) was investigated in mice, carrying a null allele of the GM-CSF gene, that were generated by gene targeting techniques in embryonic stem cells. Although steady-state hematopoiesis was unimpaired in homozygous mutant animals, all animals developed the progressive accumulation of surfactant lipids and proteins in the alveolar space, the defining characteristic of the idiopathic human disorder pulmonary alveolar proteinosis. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
576
0
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 824 publications
(611 citation statements)
references
References 35 publications
22
576
0
7
Order By: Relevance
“…delivery of a rBCG strain secreting detectable levels of GM-CSF in situ augments local immunogenicity and demonstrates significant protection against M. tuberculosis infection. GM-CSF is critical to the differentiation of myeloid cells such as DC and macrophages from haematopoietic stem cell precursors, yet in the lung it has been shown to possess unique functions in the regulation of inflammation and host defense against infectious pathogens, as well as pulmonary surfactant and alveolar cell homeostasis [23][24][25][26]. The pattern of GM-CSF production within the lung, with GM-CSF concentrations diminishing over time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…delivery of a rBCG strain secreting detectable levels of GM-CSF in situ augments local immunogenicity and demonstrates significant protection against M. tuberculosis infection. GM-CSF is critical to the differentiation of myeloid cells such as DC and macrophages from haematopoietic stem cell precursors, yet in the lung it has been shown to possess unique functions in the regulation of inflammation and host defense against infectious pathogens, as well as pulmonary surfactant and alveolar cell homeostasis [23][24][25][26]. The pattern of GM-CSF production within the lung, with GM-CSF concentrations diminishing over time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs depleted of G-CSF by a neutralizing antibody develop profound and selective neutropenia [20], but dogs similarly depleted of GM-CSF do not become neutropenic [21]. Furthermore, disruption of the G-CSF gene in knock-out mice results in chronic neutropenia [22], whereas GM-CSF knock-out mice do not become neutropenic [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that most tissue macrophages are dependent on the cytokine macrophage-colony stimulating factor (M-CSF or Csf-1) for their development, there is now evidence that microglia and LCs can form in the absence of Csf-1 ligand (Ginhoux et al, 2006(Ginhoux et al, , 2010Kondo et al, 2007;Wegiel et al, 1998). In addition, the cytokine GM-CSF thought to control mostly DC development also controls lung alveolar macrophage function (Dranoff et al, 1994).…”
Section: Microglia and The Mononuclear Phagocyte Systemmentioning
confidence: 99%